Azidophosphonium salt-directed chemoselective synthesis of (E)/(Z)-cinnamyl-1H-triazoles and regiospecific access to bromomethylcoumarins from Morita–Baylis–Hillman adducts - Karthikeyan, Soundararajan; Shobana, Radha Krishnan; Subimol, Kamarajapurathu Raju; Monica, J. Helen Ratna; Kumar, Ayyanoth Karthik Krishna (Beilstein Journal of Organic Chemistry, 2020)
The direct transformation of Morita–Baylis–Hillman (MBH) adducts into molecules of interest is a crucial process wherein allylic hydroxy-protected or halogenated MBH adducts are commonly preferred. Herein, we report an azidophosphonium salt (AzPS)-catalysed straight forward protocol for synthesising structurally demanding (E)/(Z)-cinnamyl-1H-1,2,3-triazoles and halomethylcoumarins from MBH adducts. The novel methodology, efficient catalyst, and direct utilization of MBH adducts under mild reaction conditions qualify the reported procedures as powerful synthetic tools.
Keywords: halomethylcoumarin; Morita–Baylis–Hillman adducts; organocatalyst; phosphonium salt; triazolation

(untitled) - Mamaghani, M.; Badrian, A. (Tetrahedron Lett., 2004)

(untitled) - Yadav, L. D. S.; Srivastava, V. P.; Patel, R. (Tetrahedron Lett., 2008)

(untitled) - Tu, S.; Xu, L.-H.; Yu, C.-R. (Synth. Commun., 2008)

(untitled) - Gowrisankar, S.; Kim, K.-H.; Kim, J.-N. (Bull. Korean Chem. Soc., 2008)

(untitled) - Basavaiah, D.; Rao, J. S.; Reddy, R. J. (J. Org. Chem., 2004)

(untitled) - Basavaiah, D.; Srivardhana Rao, J. (Tetrahedron Lett., 2004)

(untitled) - Zhong, W.; Lin, F.; Chen, R.; Su, W. (Synthesis, 2008)

(untitled) - Basavaiah, D.; Reddy, R. J. (Org. Biomol. Chem., 2008)

(untitled) - Basavaiah, D.; Devendar, B.; Lenin, D. V.; Satyanarayana, T. (Synlett, 2009)

(untitled) - Basavaiah, D.; Roy, S. (Org. Lett., 2008)

(untitled) - Weichert, A.; Hoffmann, H. M. R. (J. Org. Chem., 1991)

(untitled) - Basavaiah, D.; Suguna Hyma, R.; Kumaragurubaran, N. (Tetrahedron, 2000)

(untitled) - Muthiah, C.; Kumar, K. S.; Vittal, J. J.; Kumara Swamy, K. C. (Synlett, 2002)

(untitled) - Mase, N.; Wake, S.; Watanabe, Y.; Toru, T. (Tetrahedron Lett., 1998)

(untitled) - Drewes, S. E.; Emslie, N. D.; Karodia, N.; Loizou, G. (Synth. Commun., 1990)

(untitled) - Chung, Y. M.; Gong, J. H.; Kim, T. H.; Kim, J. N. (Tetrahedron Lett., 2001)

(untitled) - Chamakh, A.; M'hirsi, M.; Villiéras, J.; Lebreton, J.; Amri, H. (Synthesis, 2000)

(untitled) - Ciclosi, M.; Fava, C.; Galeazzi, R.; Orena, M.; Sepulveda-Arques, J. (Tetrahedron Lett., 2002)

(untitled) - Wang, M.-X.; Wu, Y. (Org. Biomol. Chem., 2003)

(untitled) - Keck, G. E.; Welch, D. S. (Org. Lett., 2002)

(untitled) - Marino, J. P.; Nguyen, H. N. (J. Org. Chem., 2002)

(untitled) - Ó Dálaigh, C.; Connon, S. J. (J. Org. Chem., 2007)

(untitled) - Liu, J.; Li, Q.; Cao, Z.-M.; Jin, Y.; Lin, J.; Yan, S.-J. (J. Org. Chem., 2019)

(untitled) - Reddy, C. R.; Reddy, M. D.; Srikanth, B. (Org. Biomol. Chem., 2012)

(untitled) - Reddy, C. R.; Panda, S. A.; Ramaraju, A. (J. Org. Chem., 2017)

(untitled) - Raji Reddy, C.; Panda, S. A.; Reddy, M. D. (Org. Lett., 2015)

(untitled) - Park, S. P.; Ahn, S.-H.; Lee, K.-J. (Tetrahedron, 2010)

(untitled) - Basavaiah, D.; Reddy, B. S.; Lingam, H. (Tetrahedron, 2013)

(untitled) - Kumar, K. K.; Kumar, R. M.; Subramanian, V.; Das, T. M. (Carbohydr. Res., 2010)

(untitled) - Karthik Kumar, K.; Prabu Seenivasan, S.; Kumar, V.; Mohan Das, T. (Carbohydr. Res., 2011)

(untitled) - Karthik Kumar, K.; Mohan Das, T. (Carbohydr. Res., 2011)

(untitled) - Chandrasekhar, S.; Basu, D.; Rambabu, C. (Tetrahedron Lett., 2006)

(untitled) - Sreedhar, B.; Reddy, P. S.; Kumar, N. S. (Tetrahedron Lett., 2006)

(untitled) - Singh, V.; Hutait, S.; Batra, S. (Eur. J. Org. Chem., 2009)

(untitled) - Dheer, D.; Singh, V.; Shankar, R. (Bioorg. Chem., 2017)

(untitled) - Chen, L.; Xiao, B.-X.; Du, W.; Chen, Y.-C. (Org. Lett., 2019)

(untitled) - Paul, S.; Panda, S.; Manna, D. (Tetrahedron Lett., 2014)

(untitled) - Ji, S.-Y.; Sun, Y.-M.; Zhang, H.; Hou, Q.-G.; Zhao, C.-Q. (Tetrahedron Lett., 2014)

(untitled) - Yahata, K.; Minami, M.; Watanabe, K.; Fujioka, H. (Org. Lett., 2014)

(untitled) - Werner, T. (Adv. Synth. Catal., 2009)

(untitled) - Terada, M.; Kouchi, M. (Tetrahedron, 2006)

(untitled) - Mukaiyama, T.; Kashiwagi, K.; Matsui, S. (Chem. Lett., 1989)

(untitled) - Amurrio, I.; Córdoba, R.; Csákÿ, A. G.; Plumet, J. (Tetrahedron, 2004)

(untitled) - Wang, X.; Tian, S.-K. (Tetrahedron Lett., 2007)

Mitochondrial Medicine: Volume II, Manipulating Mitochondrial Function - Cairns, A. G.; McQuaker, S. J.; Murphy, M. P.; Hartley, R. C. (Targeting mitochondria with small molecules: The preparation of MitoB and MitoP as exomarkers of mitochondrial hydrogen peroxide, 2015)

(untitled) - Fraser, K. J.; MacFarlane, D. R. (Aust. J. Chem., 2009)

(untitled) - Enders, D.; Nguyen, T. V. (Org. Biomol. Chem., 2012)

(untitled) - Golandaj, A.; Ahmad, A.; Ramjugernath, D. (Adv. Synth. Catal., 2017)

(untitled) - Jiménez Blanco, J.; García Fernández, J.; Gadelle, A.; Defaye, J. (Carbohydr. Res., 1997)

(untitled) - Buder, W.; Schmidt, A. (Chem. Ber., 1973)

Organophosphorus Chemistry - Trippett, S.; Smith, D. J. H. (Phosphines and phosphonium salts, 1975)

(untitled) - Kaye, P. T.; Musa, M. A. (Synthesis, 2002)

(untitled) - Kaye, P. T.; Musa, M. A. (Synth. Commun., 2003)

(untitled) - Hong, W. P.; Lee, K.-J. (Synthesis, 2005)

(untitled) - Kaye, P. T.; Musa, M. A.; Nocanda, X. W.; Robinson, R. S. (Org. Biomol. Chem., 2003)